2018
DOI: 10.1016/j.biomaterials.2018.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle co-delivery of wortmannin and cisplatin synergistically enhances chemoradiotherapy and reverses platinum resistance in ovarian cancer models

Abstract: Most ovarian cancer patients respond well to initial platinum-based chemotherapy. However, within a year, many patients experience disease recurrence with a platinum resistant phenotype that responds poorly to second line chemotherapies. As a result, new strategies to address platinum resistant ovarian cancer (PROC) are needed. Herein, we report that NP co-delivery of cisplatin (CP) and wortmannin (Wtmn), a DNA repair inhibitor, synergistically enhances chemoradiotherapy (CRT) and reverses CP resistance in PRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 40 publications
0
47
0
Order By: Relevance
“…Poly(lactic-co-glycolic acid) (PLGA) and poly(ethyleneg lycol) (PEG) are biomaterials that are often used for drug delivery due to their biocompatibility.Z hang et al successfully encapsulatedwortmannin (Wtmn) and amodified version of cisplatin into FDA-approved nanoparticles fabricated with PLGA-PEG. [86] They were able to successfully encapsulate the hydrophilic drug, cisplatin,i nto NPs with ah ydrophobic core by using caprylic acid modified Pt IV cisplatin prodrug (CPP) which enhanced cisplatin's hydrophobicity.Z hang et al reported that the PLGA-PEG NPss uccessfully improved the cytotoxicity (22-fold) on A2780cis cells (i.e.,c isplatin resistant cells) and displayed strong treatment synergy( CI % 0.04). Free CPP also hada ni nhibitorye ffect on mice xenografted with A2780cis cells, however required higherd oses to obtain the same effect as the co-druge ncapsulation in NPs.…”
Section: Plga-pegnanoparticlesmentioning
confidence: 99%
See 4 more Smart Citations
“…Poly(lactic-co-glycolic acid) (PLGA) and poly(ethyleneg lycol) (PEG) are biomaterials that are often used for drug delivery due to their biocompatibility.Z hang et al successfully encapsulatedwortmannin (Wtmn) and amodified version of cisplatin into FDA-approved nanoparticles fabricated with PLGA-PEG. [86] They were able to successfully encapsulate the hydrophilic drug, cisplatin,i nto NPs with ah ydrophobic core by using caprylic acid modified Pt IV cisplatin prodrug (CPP) which enhanced cisplatin's hydrophobicity.Z hang et al reported that the PLGA-PEG NPss uccessfully improved the cytotoxicity (22-fold) on A2780cis cells (i.e.,c isplatin resistant cells) and displayed strong treatment synergy( CI % 0.04). Free CPP also hada ni nhibitorye ffect on mice xenografted with A2780cis cells, however required higherd oses to obtain the same effect as the co-druge ncapsulation in NPs.…”
Section: Plga-pegnanoparticlesmentioning
confidence: 99%
“…Furthermore, previous works have reported the accumulationo fP LGA-PEG NPs in the liver and kidneys,h owever Zhang et al reported that treatment with co-encapsulated NPs in mice xenografted with A2780cis showedn oi ncrease in serum liver and kidneyt oxicity markers above normall evels. [86,[91][92][93][94][95] The co-delivery of cisplatin and Wtmn with the PLGA-PEG NPs synergistically enhanced chemoradiotherapy (CRT) and reversedc isplatin resistance. Wtmn is a phosphoinositide 3-kinase (PI3K) inhibitor that can block downstream DNA repair pathways and potently re-sensitize cancer cells.…”
Section: Plga-pegnanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations